Physicochemical properties and molecular mechanisms of different resistant starch subtypes in rice - Liang, Cheng; Xu, Haoyang; You, Hui; Zhang, Ouling; Han, Yiman; Li, Qingyu; Hu, Yungao; Xiang, Xunchao (Frontiers in Plant Science, 2024)
A significantly positive correlation exists between apparent amylose content (AAC) of rice and its resistant starch (RS) content. In this study, 72 accessions with moderate or high AAC were selected to explore the regulatory mechanisms and physicochemical properties on different proceeding types of rice RS. RS in raw milled rice (RSm), hot cooked rice (RSc), and retrogradation rice (RSr) showed a wide variation and distinct controlling mechanisms. They were co-regulated by Waxy (Wx), soluble starch synthase (SS) IIb and SSI.Besides that, RSm was also regulated by SSIIa and SSIVb, RSc by granule-bound starch synthase (GBSS) II and RSr by GBSSII and Pullulanase (PUL). Moreover, Wx had significant interactions with SSIIa, SSI, SSIIb and SSIVb on RSm, but only the dominant interactions with SSIIb and SSI on RSc and RSr. Wx was the key factor for the formation of RS, especially the RSc and RSr. The genes had the highest expression at 17 days after flowering and were beneficial for RS formation. The longer the chain length of starch, the higher the RS3 content. RSc and RSr were likely to be contained in medium-size starch granules. The findings favor understanding the biosynthesis of different subtypes of RS.